Rice grain quality: A comparison of imported varieties, local varieties with new varieties adopted in Benin - Fofana, M.; Futakuchi, K.; Manful, J.T.; Bokossa Yaou, I.; Dossou, J.; Bleoussi, R.T.M. (Elsevier, 2011)
This study was carried out in the grain quality laboratory of the Africa Rice Center in Benin to determine the physicochemical and cooking characteristics of some rice varieties consumed in Benin where is widely cultivated and consumed as a staple. The physicochemical properties of fifteen rice varieties, five imported, five previously cultivated in Benin and five upland varieties, newly developed by the Africa Rice Center were compared. Protein content ranged from 6.4 to 7.7% among the imported and previously cultivated varieties and from 10.6 to 10.8% among the newly developed varieties by the Africa Rice Center. The gel consistencies of the previously cultivated ranged from 6.0 to 71.3 mm with the exception of ADNY 11 which had a gel consistency of 100 mm while the imported and newly developed varieties had gel consistencies ranging from 95 to 100 mm. The cooking times differed among varieties. Two previously cultivated varieties – ADNY 11 and TOX LONG – had cooking times of less than 20 min while a newly developed variety, NERICA 1 had the longest cooking time of 26 min. It is suggested that greater attention be subsequently paid to grain quality characteristics in African rice breeding programs in order to meet consumer preferences on the continent.